STRATEGI GURU DALAM PENANAMAN SIKAP NASIONALISME PADA SISWA KELAS IV DI SDN WONOSEKAR - Salsabila, Lizzy; Rondli, Wawan Shokib; Fardani, Much. Arsyad (Jurnal Pendidikan Dasar Flobamorata, 2024)
This study aims to determine the teacher's strategy in instilling an attitude of nationalism in class IV SDN Wonosekar. This study uses qualitative research using case study research methods. Data collection is done by observation, interviews, and documentation. The subjects of this study were teachers and fourth grade students, totaling 25 students. Data analysis used is data reduction, data presentation, and drawing conclusions. The results showed that the strengthening of nationalism in grade IV students at SDN Wonosekar through habituation and example supported by school culture. The attitude of nationalism in grade IV students during learning includes love for the motherland, respect for the services of heroes, willingness to sacrifice, and tolerance and tolerance. The teacher's strategy at SDN Wonosekar in instilling an attitude of nationalism in students includes habituation, exemplary activities, and programmed activities that are supported by school culture